Evaluación de herramientas para el análisis forense en dispositivos móviles bajo Android, año 2022 - Cueva Cando, Alexis Ronaldo (2023)
Based on the growing popularity of mobile devices worldwide, especially Android users, there has been an increase in illegal acts against these devices, which is why forensic science requires the use of tools (software) for the analysis of these devices, so that relevant information can be collected to contribute to the country's judicial processes. In this work we propose to exhibit the tools available for the execution of a forensic analysis in equipment with Android operating system in its different versions, in addition to a comparative study of the characteristics and functionalities of the selected tools. The multiple security vulnerabilities of the Android OS up to the recent publication will be exposed. The work proposes a schematic review of the characteristics that each tool presents, considering as criteria for its estimation the multiplatform operability, costs and supported versions, as well as the functions they have. A tool will be chosen and evaluated based on the majority compliance with the parameters established for comparison and the results of the tool evaluation process will be detailed. With the finalized study it will be possible to infer the compliance with the evaluation criteria and if the tools meet the essential needs of the process, but it will be indicated that they can be adjusted to different situations that a forensic professional may face, although there are points to consider such as the license cost, the essential requirements for the operation and the functionality in different platforms. Keywords: Android, Mobile Devices Forensics, Forensic Analysis